1969
DOI: 10.1017/s0021859600022188
|View full text |Cite
|
Sign up to set email alerts
|

Effects of time and rate of nitrogen application on tillering, ‘sharp eyespot’ (Rhizoctonia solani) and yield in winter wheat

Abstract: SUMMARYVarious rates of nitrogen fertilizer were applied in early and late spring to two densities of winter wheat to examine their effects on grain yield and its components. A severe attack of ‘sharp eyespot’ (Rhizoctonia solani) allowed an assessment of the effects of the treatments on the incidence of this disease.The disease level was much higher where nitrogen was applied early and increased with increase in nitrogen up to 120 units applied; it was slightly higher at the higher density. Grain yield was sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1984
1984
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Studies by Widdowson et al (1961) and Bremner (1969) in rainfed winter wheat demonstrated reduced lodging with either unchanged or increased yield associated with in-crop application of N compared with the same amount of N applied at sowing. However, their yield levels (4-5 t ha -1 ) suggested that grain yield was limited through water or nutrient limitations, and may not be applicable to modern spring wheat germplasm capable of yielding 8 t ha -1 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Widdowson et al (1961) and Bremner (1969) in rainfed winter wheat demonstrated reduced lodging with either unchanged or increased yield associated with in-crop application of N compared with the same amount of N applied at sowing. However, their yield levels (4-5 t ha -1 ) suggested that grain yield was limited through water or nutrient limitations, and may not be applicable to modern spring wheat germplasm capable of yielding 8 t ha -1 .…”
Section: Introductionmentioning
confidence: 99%
“…anthesis, 90 % of the shoots born early will survive to produce ears, whereas shoots born towards the end of tillering have little chance of survival, thus resembling the pattern of tiller survival observed by Bremner (1969).…”
Section: Model Descriptionmentioning
confidence: 67%
“…Field studies of tillering and shoot growth (Bremner, 1969;Brooking & Kirby, 1981;Masle-Meynard & Sebillotte, 1981a, 6;Fraser, Dougherty & Langer, 1982), leaf production and growth (Gallagher, 1979;Gallagher, Biscoe & Wallace, 1979;Baker, Gallagher & Monteith, 1980) and overall cereal development (Willington, 1982) have provided empirical rules of development which can be expressed mathematically and synthesized into a detailed model of canopy development.…”
Section: Introductionmentioning
confidence: 99%
“…Ο Hay (1986), διαπίστωσε ότι η θνησιμότητα των δευτερογενών στελεχών αυξάνει λίγο μετά την επιμήκυνση των μεσογονατίων και το στάδιο σχηματισμού του τελευταίου σταχυδίου. Επίσης, έχει βρεθεί ότι η θνησιμότητα των αδελφιών επηρεάζεται από την υψηλή θερμοκρασία (Cannell, 1969;Rawson, 1971a;Ishag and Taha, 1974;Thorne and Wood, 1987), τη διαθεσιμότητα θρεπτικών στοιχείων (Bremner, 1969;Power and Alessi, 1978;Blacklow and Incoll, 1981), την πυκνότητα της φυτείας (Darwinkel, 1978), την αλατότητα (McMaster, 1997 αλλά και από το νερό (Langer, 1979;Trought and Drew, 1980;Belford, 1981;Davidson and Chevalier, 1987;Krenzer et al, 1991;McMaster et al, 1994;Blum et al, 1990;Elhani et al, 2007). Σε διάφορα πειράματα η θνησιμότητα των δευτερογενών στελεχών που καταγράφηκε, κυμάνθηκε από 7 έως 30 % (Sharma, 1995) Ο ρόλος των νεκρών ή των μη παραγωγικών δευτερογενών στελεχών στην παραγωγικότητα της φυτείας δεν είναι ξεκαθαρισμένος (Sharma, 1995).…”
Section: εκφυλισμός και νέκρωση ανθέωνunclassified